2022
DOI: 10.1111/imb.12765
|View full text |Cite
|
Sign up to set email alerts
|

Using tissue specific P450 expression in Drosophila melanogaster larvae to understand the spatial distribution of pesticide metabolism in feeding assays

Abstract: Drug metabolizing enzymes such as cytochrome P450s have often been implicated in influencing levels of pesticide toxicology and resistance. Consequently, a variety of different P450 genes and variants have been linked to pesticide metabolism. Substantially less is known in regards to which tissues these P450s contribute to pesticide metabolism. Here, we isolate the effect of different tissues in pesticide toxicology by driving the model P450 Cyp6g1 in specific tissues of Drosophila melanogaster. Fluorescent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…melanogaster dietary exposure to permethrin and cyp4e3 knockdown caused a significant elevation of oxidative stress-associated markers in the Malpighian tubules, which included lipid peroxidation based on the production of 4-hydroxynonenal; these findings have increased our understanding of the molecular mechanisms of permethrin detoxification in the Malpighian tubules [ 36 ]. These observations indicate that the fat body, midgut, and Malpighian tubules are essential tissues for detoxification [ 37 , 38 ]. In particular, the expression of Pocyp4d2 was higher in the midgut than in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster dietary exposure to permethrin and cyp4e3 knockdown caused a significant elevation of oxidative stress-associated markers in the Malpighian tubules, which included lipid peroxidation based on the production of 4-hydroxynonenal; these findings have increased our understanding of the molecular mechanisms of permethrin detoxification in the Malpighian tubules [ 36 ]. These observations indicate that the fat body, midgut, and Malpighian tubules are essential tissues for detoxification [ 37 , 38 ]. In particular, the expression of Pocyp4d2 was higher in the midgut than in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies point to relevant aspects of the toxicity mechanism, reinforcing the relevance of this alternative model for the biological sciences and health. Rotenone mediated developmental toxicity in Drosophila melanogaster [88] 2022 Characterization of a novel pesticide transporter and P-glycoprotein orthologues in Drosophila melanogaster [89] 2022 Age-related tolerance to paraquat-induced parkinsonism in Drosophila melanogaster [90] 2022 Potentiation of paraquat toxicity by inhibition of the antioxidant defenses and protective effect of the natural antioxidant, 4-hydroxyisopthalic acid in Drosophila melanogaster [91] 2022 Herbicide Roundup shows toxic effects in nontarget organism Drosophila [92] 2022 Protective capacity of carotenoid trans-astaxanthin in rotenone-induced toxicity in Drosophila melanogaster [93] 2022 Cyromazine Effects the Reproduction of Drosophila by Decreasing the Number of Germ Cells in the Female Adult Ovary [94] 2022 Low doses of the organic insecticide spinosad trigger lysosomal defects, elevated ROS, lipid dysregulation, and neurodegeneration in flies [95] 2022 Short exposure to nitenpyram pesticide induces effects on reproduction, development and metabolic gene expression profiles in Drosophila melanogaster (Diptera: Drosophilidae) [96] 2022 Using tissue specific P450 expression in Drosophila melanogaster larvae to understand the spatial distribution of pesticide metabolism in feeding assays [97] 2021 An integrated host-microbiome response to atrazine exposure mediates toxicity in Drosophila [98] 2021 Effects of some insecticides (deltamethrin and malathion) and lemongrass oil on fruit fly (Drosophila melanogaster) [99] 2021 Chronic exposure to paraquat induces alpha-synuclein pathogenic modifications in Drosophila [100] 2021 Pre-imaginal exposure to Oberon® disrupts fatty acid composition, cuticular hydrocarbon profile and sexual behavior in Drosophila melanogaster adults [101] 2021 Transcriptomic identification and characterization of genes commonly responding to sublethal concentrations of six different insecticides in the common fruit fly, Drosophila melanogaster [102] 2021 Protective effect of Catharanthus roseus plant extracts against endosulfan and its isomers induced impacts on non-targeted insect model, Drosophila melanogaster and live brain cell imaging [103] 2021 Chlordane exposure causes developmental delay and metabolic disorders in Drosophila melanogaster [104] 2021 Dietary behavior of Drosophila melanogaster fed with genetically-modified corn or Roundup ® [105] Brazilian Archives of Biology and Technology. Vol.67: e24230091, 2024 www.scielo.br/babt Cont.…”
Section: The Alternative Animal Model Drosophila Melanogaster As a Bi...mentioning
confidence: 99%
“…Previous investigations have also revealed that detoxified enzymes in insect gut tissues could mitigate the toxic effects of pesticides. For instance, the midgut-specific expression of CYP340s in diamondback moth was proved to be connected to abamectin resistance [44], and a prominent role of CYP6G1 expressed in D. melanogaster midguts was also highlighted in pesticide toxicology [45]. Combined with our finding, we preliminarily assume that the imbalanced microbiota introduced an adverse influence on larval survivorship and this consequence might be associated with the downregulation of 14 P450 genes in guts Since no difference was discovered between GD and CV larvae, we considered a negligible role of antibiotics on the expression level of P450s (Supplementary Table S3).…”
Section: The Possible Interaction Between Bacterial Colonizers and P4...mentioning
confidence: 99%